Community Schools - Jones, Chris (Educological discourse, 2014)
This article offers a summary of Community Schools. Describing the nine International Quality Standards from Community Schools, it focuses on key aspects of Community Schools and examines the implications for policy, strategy and in service senior management training. Finally, research topics are recommended.